Dosimetric impact of the positioning variation of tumor treating field electrodes in the PriCoTTF‐phase I/II trial. Issue 1 (3rd January 2021) - Nour, Youness; Pöttgen, Christoph; Kebir, Sied; Lazaridis, Lazaros; Lüdemann, Lutz; Guberina, Maja; Gauler, Thomas; Scheffler, Björn; Jabbarli, Ramazan; Pierscianek, Daniela; Sure, Ulrich; Schmidt, Teresa; et al.
Abstract: Purpose: The aim of the present study based on the PriCoTTF‐phase I/II trial is the quantification of skin‐normal tissue complication probabilities of patients with newly diagnosed glioblastoma multiforme treated with Tumor Treating Field (TTField) electrodes, concurrent radiotherapy, and temozolomide. Furthermore, the skin‐sparing effect by the clinically applied strategy of repetitive transducer array fixation around their center position shall be examined. Material and Methods: Low‐dose cone‐beam computed tomography (CBCT) scans of all fractions of the first seven patients of the PriCoTTF‐phase I/II trial, used for image guidance, were applied for the dosimetric analysis, for precise TTField transducer array positioning and contour delineation. Within this trial, array positioning was varied from fixation‐to‐fixation period with a standard deviation of 1.1 cm in the direction of the largest variation of positioning and 0.7 cm in the perpendicular direction. Physical TTField electrode composition was examined and a respective Hounsfield Unit attributed to the TTField electrodes. Dose distributions in the planning CT with TTField electrodes in place, as derived from prefraction CBCTs, were calculated and accumulated with the algorithm Acuros XB. Dose‐volume histograms were obtained for the first and second 2 mm scalp layer with and without migrating electrodes and compared with those with fixed electrodes in an average position. Skin toxicity was quantified according to Lyman's model. Minimum doses in hot‐spots of 0.05 cm 2 and 25 cm 2 ( Δ D0.05cm 2, Δ D25cm 2 ) size in the superficial skin layers were analyzed. Results: Normal tissue complication probabilities (NTCPs) for skin necrosis ranged from 0.005% to 1.474% (median 0.111%) for the different patients without electrodes. NTCP logarithms were significantly dependent on patient ( P  < 0.0001) and scenario ( P  < 0.0001) as classification variables. Fixed positioning of TTField arrays increased skin‐NTCP by a factor of 5.50 (95%, CI: 3.66–8.27). The variation of array positioning increased skin‐NTCP by a factor of only 3.54 (95%, CI: 2.36–5.32) ( P  < 0.0001, comparison to irradiation without electrodes; P  = 0.036, comparison to irradiation with fixed electrodes). NTCP showed a significant rank correlation with D25cm 2 over all patients and scenarios (rs  = 0.76; P  < 0.0001). Conclusion: Skin‐NTCP calculation uncovers significant interpatient heterogeneity and may be used to stratify patients into high‐ and low‐risk groups of skin toxicity. Array position variation may mitigate about one‐third of the increase in surface dose and skin‐NTCP by the TTField electrodes.